PENGARUH TIMBAL-BALIK ANTARA PEMBAYARAN DIVIDEN DAN PERTUMBUHAN MODAL SENDIRI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sofiati Sofiati (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
This study extends previous research on dividend policy and funding decisions. Previous studies have focused on dividend policy or funding decisions alone,to determine the factors that influences.This study aims to determine the mutual influence between dividend payout and capital growth. The authors would like to exame that there are similarities between the factors that affect the distribution of dividends and capital growth include profitability,agency cost,and retained earnings. In this research,the sample comprises of 72 active stocks listed and traded in Indonesia Stock Exchange during the periode of 2011-2015. The test results demonstrate the usefulness of the model testing using indicators overall goodness of fit to meet the criteria recomended level of fitness. By using the non-statistical measure such absolute goodness of fit and parsimony goodness of fit value exceeds recomended levels, it has indicated a good fit between the data with the model proposed research.